Gender matters in physiotherapy. (18th November 2022) - Stenberg, Gunilla; Fjellman-Wiklund, Anncristine; Strömbäck, Maria; Eskilsson, Therese; From, Carin; Enberg, Birgit; Wiklund, Maria
ABSTRACT: The World Health Organization states that gender has implications for health across the course of a person's life in terms of norms, roles and relations. It also has implications in rehabilitation. In this article, we argue the need of gender perspectives in the field of physiotherapy; gender matters and makes a difference in health and rehabilitation. We highlight a number of central areas where gender may be significant and give concrete examples of social gender aspects in physiotherapy practice and in diverse patient groups. We also discuss why it can be important to consider gender from an organizational perspective and how sociocultural norms and ideals relating to body, exercise and health are gendered. Further we present useful gender theories and conceptual frameworks. Finally, we outline future directions in terms of gender-sensitive intervention, physiotherapy education and a gendered application of the ICF model. We want to challenge physiotherapists and physiotherapy students to broaden knowledge and awareness of how gender may impact on physiotherapy, and how gender theory can serve as an analytical lens for a useful perspective on the development of clinical practice, education and research within physiotherapy.